ANALISIS KINERJA APARATUR BADAN PENDIDIKAN DAN PELATIHAN KOTA LUBUKLINGGAU - Rozikin, Muhammad (Jurnal Governance dan Administrasi Publik, 2017)
This study aims to determine whether the performance of officials at the Lubuk linggau City Education and Training Agency has carried out their duties and functions in accordance with the Lubuk linggau City Regional Regulation Number 09 of 2005 concerning the Organizational Structure and Work Procedures of Regional Technical Institutions), which is enhanced by the Lubuk linggau City Regional Regulation Number. 03 Year 2008 concerning Organization and Work Flow arrangement Technical Institute regions (regional Gazette Lubuk linggau Year 2008 Number 05) followed by the Mayor Regulation Lubuk LinggauNo. 31 Year 2008 on translation of Duty and Function of Education and Training Agency Lubuk linggau. The results of this study use three points of view, namely productivity, service quality and responsiveness and are relevant to the main tasks and functions of the City Education and Training Agency Lubuklinggau. Productivity not only measures the level of efficiency but also the effectiveness of services. Effectiveness is the level of achieving goals through the implementation of the duties and responsibilities of the apparatus at the Lubuk linggau City Education and Training Agency. Quality of service is community satisfaction with the services received from the bureaucratic apparatus, Responsiveness is the ability of the apparatus to recognize community needs, arrange service agendas and priorities and develop public service programs in accordance with the needs and aspirations of the community. For more details, please see the summary page.